PENGARUH KEPUASAN KERJA KARYAWAN DAN IKLIM ORGANISASI TERHADAP KOMITMEN KARYAWAN PADA DINAS PEKERJAAN UMUM KABUPATEN LOMBOK TIMUR - Zulkarnaen Zulkarnaen; Nizar Hamdi (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the effect of job satisfaction (X1) and organizational climate (X2) both jointly and individually on employee work commitment (Y) at the East Lombok District Public Works Office and also to determine the independent variables more dominant influence between job satisfaction (X1) and organizational climate (X2) on employee work commitment (Y) at the East Lombok District Public Works Office. This type of research is associative because it analyzes the influence relationship between the independent variable and the dependent variable. The number of samples used in this study were 66 employees. While the data collection tool used a questionnaire and the data analysis tool used multiple regression tests with a hypothesis test tool using the F test, t test and β test. Based on the results of the F test (together) the variable job satisfaction (X1) and organizational climate variables together have a significant effect on the variable employee work commitment. This is evidenced by the significance value of F of 0.041 which is smaller than the research significance (Sig.a) = 0.050 (5%). Based on the results of the t test (partial or individually) the variable of job satisfaction (X1) has a significant effect on the variable of employee work commitment. This is evidenced from the results of the significance of the t test of Sig.t = 0.017 < Sig.a = 0.050. Based on the results of the t test (partial or individually) organizational climate variables individually have a significant effect on the employee work commitment variable. This is evidenced by the results of the significance of the t test of Sig.t 0.020 < Sig.a = 0.050. Based on the results of multiple regression, it can be seen that the variable that has the largest beta standard (β coefficient) is job satisfaction, namely with the coefficient β1 = 0.495 compared to the β value of the organizational climate variable, namely β2 = 0.416. Shows that the independent variable that has a dominant influence is Job Satisfaction.